Sociodemographic associations of longitudinal adiposity in youth with type 1 diabetes. Issue 8 (14th September 2018) - Kahkoska, Anna R.; Shay, Christina M.; Couch, Sarah C.; Crandell, Jamie; Dabelea, Dana; Gourgari, Evgenia; Lawrence, Jean M.; Liese, Angela D.; Pihoker, Catherine; Reboussin, Beth A.; The, Natalie; Mayer‐Davis, Elizabeth J.
Abstract : Excess adiposity is common in youth with type 1 diabetes, yet little is known about the sociodemographic factors that predict longitudinal trajectories of body fat. We analyzed data from 363 females and 379 males with type 1 diabetes over ~9 years of follow‐up (mean baseline age 12.8 ± 2.3 years in females, 13.2 ± 2.4 years in males). Estimated body fat percentage (eBFP) was calculated with validated sex‐ and race/ethnicity‐specific equations. Group‐based modeling identified three eBFP trajectories for each sex. All female trajectories showed gradual increases, while male trajectories showed gradual decreases (<5% in eBFP) that plateaued around 7 years of diabetes duration. Female trajectories showed differences in baseline eBFP: Group F1 (38.0%), mean eBFP 27.8 ± 3.0%: Group F2 (47.9%), mean eBFP 33.9 ± 3.0%: and Group F3 (14.1%), mean eBFP 41.7 ± 4.1%. Male trajectories also showed differences in baseline eBFP: Group M1 (57.2%), mean eBFP 22.0 ± 3.0%: Group M2 (30.9%), mean eBFP 33.9 ± 3.0%: and Group M3 (12.9%), mean eBFP 36.1 ± 3.7%. In multinomial models, adjusted for clinical factors (eg, insulin regimen, insulin dose, and hemoglobin A1c), females who reported a single‐parent household (adjusted odds ratio [aOR] = 3.34, 95% confidence interval [CI]: 1.49, 7.47), parental education of less than a college degree (aOR = 3.79, 95% CI: 1.60, 9.60), and a lack of private health insurance (aOR = 3.74, 95% CI: 1.45, 9.60), and a household income of less than $75 000 per year (aOR = 3.13, 95% CI: 1.27, 7.70) were approximately three to four times more likely to be in the highest eBFP trajectory group relative to the lowest eBFP trajectory group. Males who reported a household income of <$75 000/year were almost twice as likely to be in the Group M3 than the Group M1 in the unadjusted model only (aOR = 1.79, 95% CI: 0.91, 4.01 vs unadjusted OR: 2.48, 95% CI: 1.22, 5.06). Lower socioeconomic status may be associated with excess body fat throughout adolescence in type 1 diabetes, particularly among females.